2017
DOI: 10.1007/978-3-319-72905-3_4
|View full text |Cite
|
Sign up to set email alerts
|

A Federated Enterprise Architecture and MBSE Modeling Framework for Integrating Design Automation into a Global PLM Approach

Abstract: PLM and Design Automation (DA) are two interdependent and necessary approaches to increase the performance and efficiency of product development processes. Often, DA systems' usability suffers due to a lack of integration in industrial business environments stemming from the independent consideration of PLM and DA. This article proposes a methodological and modeling framework for developing and deploying DA solutions within a global PLM approach. This framework supports the identification of DA potentials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Thus, designers employed at large companies might not receive latest information from software vendors and are usually not directly involved in the specification and implementation of design automation solutions. A potential means to support designers is the development of methods to enable designers to identify and specify design automation task themselves (Vosgien et al, 2017). Considering knowledge about design automation, interestingly, most SMEs have knowledge about design automation and occasionally, design automation is also applied in SMEs, as depicted in Figure 8.…”
Section: Current State Of Design Automation and Corresponding Potentialmentioning
confidence: 99%
“…Thus, designers employed at large companies might not receive latest information from software vendors and are usually not directly involved in the specification and implementation of design automation solutions. A potential means to support designers is the development of methods to enable designers to identify and specify design automation task themselves (Vosgien et al, 2017). Considering knowledge about design automation, interestingly, most SMEs have knowledge about design automation and occasionally, design automation is also applied in SMEs, as depicted in Figure 8.…”
Section: Current State Of Design Automation and Corresponding Potentialmentioning
confidence: 99%
“…CAx [30] or design automation [31], [32]. Still, the works presented in [33], [34] have shown that the principles of enterprise architecture are also applicable in a PLM context. Hence, in this work methods of enterprise architecture are also used for the design and monitoring of PLM strategies.…”
Section: Enterprise Architecturementioning
confidence: 99%